A New Technique For Treatment of Imperforate Hymen By Aortic Punch - Alptekin, Hüsnü; Gezginç, Kazım; Yazıcı, Fatma (Gynecology Obstetrics & Reproductive Medicine, 2012)
To present a case of imperforate hymen treated by aortic punch without damaging the structure of the hymen. A 15-year-old girl was admitted to our clinic with history of pelvic pain for 3 months. On inspection of external genitalia, a bulging bluish membrane was seen on retracting the labia without a patent hymenal orifice. Suprapubic ultrasonographic examination demonstrated a large hematocolpos measuring 17x10 cm and hematometra measuring 3x4 cm. The hymen was perforated to 0.5 cm in diameter by an aortic punch from the middle of the distended and imperforate hymenal membrane. Blood in the vagina was drained using irrigation with a saline solution. Postoperative period was uneventful. The patient was followed up for 6-months; the patient was asymptomatic and had regular normal menstrual cycles and normal pelvic ultrasonography. Hymen protection is important in different ethnic groups and countries as it is in our country, when treatment is planned, the sociocultural values of the society should be considered.